The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1039/an9891400137
|View full text |Cite
|
Sign up to set email alerts
|

Determination of iron species in wine by ion-exchange chromatography-flame atomic absorption spectrometry

Abstract: The direct coupling of ion-exchange chromatography to flame atomic absorption spectrometry (AAS) has been achieved by employing a Babington type nebuliser. The system enables all the processes on the column to be followed directly at flow-rates of between 1 and 5 ml min-1. The potential of the system was investigated for the determination of various iron species in synthetic samples containing iron(II) and iron(III) in ionic or chelated form by employing various ion-exchange (Dowex 50-X8, Dowex 1-X8) and sorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…A useful approach to overcome such difficulties is to couple various chromatographic and optical spectrometric methods (Ajlec and Stupar 1989). In the present study, gel filtration analysis showed that oxalic acid and Mn appeared in the same fraction of the supernatant with the ratio of oxalic acid to Mn of 1.12, suggesting that there were sufficient amounts of oxalic acid to chelate Mn.…”
Section: Discussionmentioning
confidence: 94%
“…A useful approach to overcome such difficulties is to couple various chromatographic and optical spectrometric methods (Ajlec and Stupar 1989). In the present study, gel filtration analysis showed that oxalic acid and Mn appeared in the same fraction of the supernatant with the ratio of oxalic acid to Mn of 1.12, suggesting that there were sufficient amounts of oxalic acid to chelate Mn.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, accurate and fast determination of Fe(III) is an important issue in the environment and in biological systems. Up to now, numerous methods have been developed for the detection of Fe(III), including flame atomic absorption spectroscopy [14], mass spectrometry [15], electrochemical [16], and fluorescence detection [17][18][19][20][21][22][23][24][25][26]. Among these methods, fluorescence detection is a favorable method due to their high sensitivity, selectivity and fast detection.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Tremendous efforts have been made to develop sensitive Fe 31 monitoring approaches, including UV-Vis spectrophotometry, 4 inductively coupled plasma mass spectrometry, 5 flame atomic absorption spectrometry, 6 voltammetry, 7 fluorescence spectrophotometry. [8][9][10] Among these approaches, fluorescence spectroscopy is particularly promising owing to its simplicity, high sensitivity, and ability to facilitate real-time detection.…”
mentioning
confidence: 99%